The Poet as Activist: Chronotopes of San Francisco in the Poetry of Lawrence Ferlinghetti (Papers in Arts and Humanities, 2022)
The impact of one’s economic, cultural and political contributions is vital to a city’s welfare. Activism, however, is a crucial component of community life, which has determined the real meaning of individual freedom through the efforts of the social actors of the last century. In this respect, the literary texts of the Beat Generation thoroughly portray the relation between time and space and the way in which it is connected to social action. From a geocritical approach, the chronotopes found in the poetry of Lawrence Ferlinghetti, offer the reader an authentic taste of San Francisco, during the second half of the twentieth century, as well as the Beats’ perspective on one’s emergence and evolution in the metropolis during the post-war era. Space and time foster the evolution of group identity and in the same time, they shape the development of social and political endeavors. This research focuses on the intersections between time, people and creative places and seeks to portray the city, as a sociocultural construct from the point of view of a poet and an activist.
Keywords: time; city; poet; activist; San Francisco